Influence of the Number of Parallel-Joints on Size Effect of Elastic Modulus and Characteristic Elastic Modulus - Hu, Gaojian; Ma, Gang; Liang, Wenxu; Song, Leibo; Fu, Wei (Frontiers in Earth Science, 2022)
The number of joints existing in the rock affects the elastic modulus of the rock, and the relationship has not been obtained. In this paper, 10 numerical models are established by numerical simulations to study the effect of the number of parallel joints on the size effect of rock elastic modulus. The research shows that there is a power function relationship between the elastic modulus and the number of parallel joints, and a negative exponential relationship between the elastic modulus and the rock size, and their special mathematical models are given. The paper also obtains special form of the relationships between the characteristic size of rock elastic modulus, the characteristic elastic modulus and the number of parallel joints.